SOD1 gene polymorphisms in sudden sensorineural hearing loss. (3rd May 2016) - Kitoh, Ryosuke; Nishio, Shin-Ya; Ogawa, Kaoru; Okamoto, Makito; Kitamura, Ken; Gyo, Kiyofumi; Sato, Hiroaki; Nakashima, Tsutomu; Fukuda, Satoshi; Fukushima, Kunihiro; Hara, Akira; Yamasoba, Tatsuya; et al.
Abstract: Conclusion The results suggest that SOD1 rs4998557 could be associated with susceptibility to SSNHL in the Japanese population.Objectives To assess the gene association with sudden sensorineural hearing loss (SSNHL).Methods A two-stage case control study was conducted to explore the relationship of the candidate genes to SSNHL. The 192 gene samples from SSNHL patients registered in the intractable inner ear disease gene bank were enrolled. As the candidate genes, 39 SNPs from 31 genes were selected for the first stage study. The second stage study examined whether the SOD1 gene polymorphisms, defined by significant differences between cases and controls in the first stage study, are associated with SSNHL.Results Significant differences were observed in four SNPs from three genes, Glutathione-S-transferase pai 1 (GSTP1), proteine kinase C heta (PRKCH), and superoxide dismutase 1 (SOD1), in terms of allele frequency between SSNHL patients and HapMap controls. In the SOD1 gene, a significant difference was observed in the dominant model study of the SNP rs4998557 in the second stage study. Furthermore, as a result of dividing SSNHL patients based on the clinical data, the difference was more apparent in the case of the over 60 dB group and the tinnitus–positive group.